2017
DOI: 10.1242/jcs.200204
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the targeting of tail-anchored proteins to subcellular compartments in mammalian cells

Abstract: Tail-anchored (TA) proteins contain a single transmembrane domain (TMD) at the C-terminus that anchors them to the membranes of organelles where they mediate critical cellular processes. Accordingly, mutations in genes encoding TA proteins have been identified in a number of severe inherited disorders. Despite the importance of correctly targeting a TA protein to its appropriate membrane, the mechanisms and signals involved are not fully understood. In this study, we identify additional peroxisomal TA proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(143 citation statements)
references
References 73 publications
14
125
0
Order By: Relevance
“…Additionally, in a high‐throughput interaction study, MIRO1 was identified as a PEX19 interaction partner 37. These findings are also consistent with the known organelle targeting signals: MIRO1 possesses a transmembrane domain (TMD) with relatively low hydrophobicity (GRAVY, 1.3) and a moderate net charge in the tail region (1.9), which based on our previous work would be indicative of a TA protein that localises predominantly to mitochondria but has a potential for peroxisomal targeting 34. Overall, our findings support a dual localisation of MIRO1 at mitochondria and peroxisomes.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, in a high‐throughput interaction study, MIRO1 was identified as a PEX19 interaction partner 37. These findings are also consistent with the known organelle targeting signals: MIRO1 possesses a transmembrane domain (TMD) with relatively low hydrophobicity (GRAVY, 1.3) and a moderate net charge in the tail region (1.9), which based on our previous work would be indicative of a TA protein that localises predominantly to mitochondria but has a potential for peroxisomal targeting 34. Overall, our findings support a dual localisation of MIRO1 at mitochondria and peroxisomes.…”
Section: Resultssupporting
confidence: 82%
“…As MIRO1 can alter peroxisome distribution and motility, it is likely one of the yet unidentified adaptors for microtubule‐based peroxisome motility in mammalian cells. This assumption is further supported by recent findings showing that mitochondria and peroxisomes share many TA membrane proteins and their functions due to their close cooperation and co‐evolution in mammalian cells 34. During the submission of our work, Okumoto et al 55 revealed that distinct MIRO1 splice variants show different targeting to mitochondria and peroxisomes in HEK cells, with MIRO1‐variant 4 being more specific for peroxisomes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, numerous TA proteins are dually targeted to both peroxisomes and mitochondria [23]. This targeting appears to be largely dependent on the biochemical properties of their C-terminal amino acid sequence (principally the hydrophobicity of the TMD and the net charge in the tail region) and, as such, it can be characterized and used to predict the targeting of TA proteins [12]. Interestingly, Miro1 has an identical TMD hydrophobicity and tail charge to that of Mff, another dually targeted protein involved in mitochondrial and peroxisomal division [24].…”
Section: Targeting and Pex19 Bindingmentioning
confidence: 99%
“…These characteristic properties dictate that TA proteins are post-translationally sorted to their target membrane with the N-terminus facing the cytosol 23 . In another recent study we investigated the targeting properties of TA proteins, discovering the importance of interplay between TMD hydrophobicity and tail-charge, and developed a statistical model to predict cellular localization of TA proteins based on these physicochemical parameters 24 . Using this bioinformatics prediction tool we identified an isoform of ACBD4 (isoform 2), a predicted TA protein of unknown function and localization, as a potential peroxisomal protein and confirmed this by expression of Myc-ACBD4iso2 in COS-7 cells 24 .…”
Section: Introductionmentioning
confidence: 99%